Lived Experience of Students in a Remedial Mathematics Class - Guirguis, Joan Mel (8ISC Proceedings: Arts and Education; 8ISC Proceedings: Arts and Education, 2022)
Students who do not pass the entrance mathematics examination in a tertiary school are required to take a remedial mathematics class. In remedial education, the goal is to get the student to the mainstream. The remedial courses are designed to give students the skills needed for tertiary-level courses. This study pursues the lived experience of students in a remedial mathematics class. There are 9 males and 5 females who are participants in this study. Their ages range from 19 to 28. These participants were selected using purposive sampling. The needed information was generated using the student’s journal for the remedial mathematics class. Journal writing allows one to reflect, to further investigate deeper into the heart of the words, beliefs, and behaviors. Writing one’s thoughts allows us to step into one’s mind and reach further into the interpretation of the behavior and beliefs. The finding showed the social and emotional learning of students in a remedial mathematics class. The finding also revealed the coping and self-regulating strategies the students used in the remedial mathematics class. Keywords : Underprepared Student, Mathematics Remedial Class, Journal Writing, Lived Experience, Learning Emotions